The relationships between wrist joint position sense, anthropometric characteristics and grip strength of the hand in healthy individuals - Abalay, Arzu; Cemel, Yakup; Varhan, Berrak; Yavuzer, Melek Güneş (My University, 2024)
Objective: The hand is an extremely unique structure with its own characteristics that should be better understood. To determine the relationship between joint position sense (JPS), hand anthropometrics, and grip strength (GS) in healthy individuals. Methods: Both hands of 50 healthy adults were evaluated. The anthropometric characteristics (AC) were determined using small paper insertion tape. Hand and finger strength were measured using hand dynamometry and a pinchometer, respectively. The wrist JPS was evaluated for wrist flexion, extension, and deviations via a position error test using a goniometer. Results: AC and GS were positively correlated with both the dominant and non-dominant sides in all parameters (p<0.05). There was a significant positive relationship between palmar GS and wrist flexion JPS error on the dominant side (p=0.039, r=0.292) and on the non-dominant side (p=0.033, r=-0.303). There was no significant relationship between JPS and the AC of any other GS parameters (p>0.05). Conclusion: The use of anthropometric data in calculating GS, as well as other complimentary data, can be utilized to determine the type and diversity of exercise for physiotherapy and rehabilitation program organization. The results showed a weak correlation between wrist JPS, AC, and GS. In conclusion, our study showed that AC can be used as an indicator of GS, but GS alone is insufficient to indicate joint position.

Amaç: El, daha fazla anlaşılması gereken kendine has özellikleri ile son derece benzersiz bir yapıdır. Sağlıklı insanlarda eklem pozisyon duyusu (EPD), el antropometrisi ve kavrama kuvveti (KK) arasındaki ilişkiyi belirlemek amacıyla yapılmıştır. Gereç ve Yöntem: Elli sağlıklı yetişkinin her iki eli değerlendirildi. Antropometrik özellikler (AÖ) ölçülürken referans noktaları küçük kağıtlarla işaretlendi. El ve parmak kuvveti sırasıyla el dinamometrisi ve pinç metre ile ölçüldü. Bilek eklemi pozisyon hissi, bilek fleksiyonu, ekstansiyonu ve deviasyonları için gonyometre ile pozisyon hata testi ile değerlendirildi. Bulgular: AÖ ve KK, tüm parametrelerde hem baskın hem de baskın olmayan taraf için pozitif korelasyon gösterdi (p<0,05). Antropometrik ölçümler ile eklem pozisyon hisleri arasında istatistiksel olarak anlamlı ilişki saptanmadı (p>0,05). Fleksiyon yönünde eklem pozisyon hissi ile palmar KK arasında pozitif yönde anlamlı ilişki bulundu (p<0,05). Lateral KK ile hem fleksiyon hem de ekstansiyon yönünde el bileği eklem pozisyon hissi ile negatif yönde anlamlı ilişki bulundu (p<0,05). Sonuç: KK’nin hesaplanmasında antropometrik verilerin yanı sıra diğer tamamlayıcı verilerin kullanılması, fizyoterapi ve rehabilitasyon programının belirlenmesinde, egzersiz türüne ve çeşitliliğine karar vermek için kullanılabilir. Bu çalışmanın bulguları; el bileği eklem pozisyon hissi, antropometrik özellikler ve KK arasında zayıf bir korelasyon olduğunu göstermiştir. Sonuç olarak, çalışmamız antropometrik özelliklerin KK’nin bir göstergesi olarak kullanılabileceğini, ancak KK’nin eklem pozisyon hissini göstermede yetersiz olduğunu göstermektedir.
Sağlıklı bireylerde el bileği eklem pozisyon hissi, kavrama gücü ve elin antropometrik özellikleri arasındaki ilişki
Keywords: Anthropometric Variables; Grip Strength; Pinch Strength; Wrist Joint Position Sense; El Bileği Eklem Pozisyon Hissi; Antropometrik Ölçümler; El Kavrama Kuvveti; Parmak Kavrama Kuvveti